Aplikasi Sistem Informasi Barang Persediaan (ATK) Studi Kasus: Unit Pelaksana Pelayanan terpadu Satu Pintu Kabupaten Administrasi Kepulauan Seribu - Haki Ahmadi; Syukri Nazar (Ensiklopedia of Journal, 2019)
Kantor Pelayanan Terpadu Satu Pintu (KPTSP) of Kepulauan Seribu District Administration is a regional work unit set up based on Regional Regulation Number 12 year 2013 concerning the implementation of One Stop Services. This work unit has a duty to serve the licensing and non-licensing applications in accordance with Regional Regulation Number 7 year 2017, KPTSP has changed the nomenclature to become Unit Pelaksana Pelayanan Terpadu Satu Pintu (UPTSP). UPPTSP has several levels of service points including Provincial / Dinas, City / District, Kelurahan levels. At the Dinas and Kota / Kabupaten levels, there are many requests. The work process from the beginning of entering the file through the queue until the submission of documents to the applicant has not been well organized, so there are still some obstacles in the licensing process. Constraints experienced include those from logistic management in the form of Dinas Stationery in each UPPTSP at the District and Kelurahan levels. The supply has expired, the UPPTSP in Kelurahan level wants to submit a request for goods must fill the form of an application to apply for used goods and must spend 1 day or even 2 days for sending trips request to land to be able to get the goods requested from the Regency Level UPPTSP. Because the Adm Regency UPPTSP. The Thousand Islands are within the administrative territory of the Thousand Islands District Administration, one of the Provincial Governments of DKI Jakarta. The number of Kelurahan in the District of Thousand Islands Administration is 6, namely Kelurahan Pulau Kelapa, Kelurahan Pulau Harapan, Kelurahan Pulau Panggang, Kelurahan Pulau Tidung, Kelurahan Pulau Pari, and Kelurahan Pulau Untungjawa. Based on the problems, it takes an inventory information management system that can help employees of the District UPPTSP and the Kelurahan Level UPPTSP in managing Inventory Items and Demand for Consumable Goods. This information system design method uses Object Oriented Analysis Design (OOAD) through the UML and HTML Boostrap approaches for user prototypes. With this information system, it is expected that it will facilitate employees in the process of managing and requesting consumable goods.